43. Intraoperative neurophysiological monitoring in spine surgery: A significant tool for neuronal protection and functional restoration. Issue 12 (December 2017) - Rizzo, V.; Scibilia, A.; Raffa, G.; Quartarone, A.; Visocchi, M.; Germanò, A.; Tomasello, F.; Girlanda, P.
Abstract : Although there is recent evidence for the role of intraoperative neurophysiological monitoring (IONM) in spine surgery, there are no uniform opinions on the optimal combination of the different tools. We analyzed the impact of the multimodal IONM (mIONM) on the preservation of neuronal structures and on functional restoration in a prospective series of our patients who underwent spine surgery. The mIONM approach in spine surgery involves the evaluation of somatosensory evoked potentials (SEPs) and motor evoked potentials (MEPs) with electrical transcranial stimulation, including the use of a multipulse technique with multiple myomeric registration of responses from limbs, and a single-pulse technique with D-wave registration through epi- and intradural recording, and free running and evoked electromyography. We observed an improvement of neurological status in 50% of the patients. The D-wave registration was the most useful intraoperative tool, especially when MEP and SEP responses were absent or poorly recordable. Our preliminary data confirm that mIONM plays a fundamental role in the identification and functional preservation of the spinal cord and nerve roots. It is highly sensitive and specific for detecting and avoiding neurological injury during spine surgery and represents a helpful tool for achieving optimal postoperative functional outcome.